Pengaruh Kompensasi, Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Telkom Corporate University PT Telkom Indonesia - Ariesta Anindra Putra; Ari Pradhanawati; Widiartanto Widiartanto (Universitas Diponegoro, 2017)
Every company needs the resources that have important influence to achieve success. Success in achieving the organization's goals came from the behavior of its own employees therefore the employees that make up the structure of the organization and take advantage of technology. Performance of the employee is influenced by several factors such as compensation, motivation and Working discipline. Poor performance of the employee caused by low compensation, lack of motivation and a poor working discipline at Telkom Corporate University.This study aims to identify and explain the influence of compensation, motivation and Working discipline on the performance of the employee of Telkom Corporate University. This research uses explanatory type approach, against 69 respondents with sampling purposive technique. Data collection techniques in this study using the technique of collecting data through questionnaires and interviews. The analysis technique used is quantitative. Quantitative analysis using validity test, reliability test, cross tabulation, correlation coefficient, coefficient of determination, simple and multiple regression analysis, as well as the significance test (t test and F test) with the help of SPSS version 16.0 for Windows.The results of statistical analysis known partial influence between compensation on performance of the employee by 27.4%. Then motivation to performance of the employee by 17.8%. while for the working discipline on the performance of the employee by 35%. Simultaneous influence of the influence of compensation, motivation and Working discipline on the performance of the employee is 34.2%, while 65.8% are influenced by other factors.Recommendations for improving the performance of employees to the company to increase its attention to the work compensation, motivation and Working discipline which in turn will ultimately increase performance of the employee.